MENGKAJI MODEL PENGENDALIAN POPULASI AEDES AEGYPTI DENGAN STERILE INSECT TEHNIQUE (SIT) DAN KOMBINASINYA DENGAN INSEKTISIDA - Wati, I; Ratianingsih, R; Jaya, Agus Indra (Univ. Tadulako, 2014)
Dengue fever is one of disease which can be transmited by Aedes aegypti. However the prevention on this disease is become global concern. One approche that can be done is by controlling of mosquito population. Related to that issue, this study was done by an application of potryagyn maximum principle in optimal control theory, based on Sterile Insect Technique (SIT). It can be done biologically by introduction of male sterile mosquito (mutan which can be produce by mutagen such as gamma radiation) into the population. It expected that the number of sterile mosquitos will increase by the time. Our result showed that the population of juvenile, immature male and female mosquitos, fertile male and female, and also sterile male mosquito on the population will grow and reach the stagnan condition after 50 days. Those data indicate that the number of sterile male will increase without any reduction of the population itself. If this method be combained with insecticide chemical method, the population of mosquitos can be reduced/eliminated efectively.